Maxwellian rate coefficients for electron-impact ionization of W26+. (6th July 2018) - Kynienė, A; Merkelis, G; Šukys, A; Masys, Š; Pakalka, S; Kisielius, R; Jonauskas, V
Abstract: Excitation-autoionization (EA) and direct ionization (DI) Maxwellian rate coefficients (MRC) are presented for the levels of the ground configuration of the W 26+ ion. The study of EA and DI cross sections is performed by applying the Dirac–Fock–Slater method within the level-to-level distorted-wave approximation including radiative damping. Excitations to the high- nl shells ( n ≤ 25) are taken into account for the EA process. It is shown that electron-impact ionization from the different levels of the ground configuration produces a significant variation of MRC. Excitations to configurations with energy levels that straddle the ionization threshold play the main role in enhancing MRC for the highest level of the ground configuration. The difference of 40% among the EA MRC is determined for the levels of the ground configuration.